A primer of quantum chemistry - Goodrich, F. C. (Wiley-Interscience, 1972)
Finite dimensional vector spaces - Huckel molecular orbital theory - Function spaces and linear operators - Quantum mechanics for bound states - The central field problem - Perturbation theory - Electron spin - Atomic structure - The variation method - The delta world - Diatomic molecules - Symmetry: localized and nonlocalized molecular orbitals - Appendices.